Image of the Other by Al-Muhassin Al-Tanukhi - Shakhatreh , Khawla; Maqdadi , Hisham (Journal of Ecohumanism, 2024)
The research investigates studying the image of the other in the books of Al-Muhassin Al-Tanukhi. The research focused on defining the other and the beginnings of the formation of his image in Arab-Islamic culture, in the Qur’anic text, and in the writings of travelers and geographers. It then explains the image of the other in Al-Muhassin Al-Tanukhi’s writings. The research concluded that his image of the other is not stereotypical according to a preconceived view because he acts and recognizes the difference between the other. The images presented in the study varied across three main perspectives. First, there was a portrayal of admiration for the other, which did not culminate in a sense of amazement due to perceived cultural superiority. Second, a positive image of the other was offered. Lastly, disapproval was expressed stemming from a lack of comprehension. Furthermore, the research examined the methodology of narrative presentation, categorizing it into two distinct structures. The first structure is characterized by its simplicity, relying solely on a linear narration of events or stories. In contrast, the second structure is more complex, involving what is referred to as the phenomenon of narrative generation. This approach incorporates intricate elements such as characters and situations. The research investigates studying the image of the other in the books of Al-Muhassin Al-Tanukhi. The research focused on defining the other and the beginnings of the formation of his image in Arab-Islamic culture, in the Qur’anic text, and in the writings of travelers and geographers. It then explains the image of the other in Al-Muhassin Al-Tanukhi’s writings. The research concluded that his image of the other is not stereotypical according to a preconceived view because he acts and recognizes the difference between the other. The images presented in the study varied across three main perspectives. First, there was a portrayal of admiration for the other, which did not culminate in a sense of amazement due to perceived cultural superiority. Second, a positive image of the other was offered. Lastly, disapproval was expressed stemming from a lack of comprehension. Furthermore, the research examined the methodology of narrative presentation, categorizing it into two distinct structures. The first structure is characterized by its simplicity, relying solely on a linear narration of events or stories. In contrast, the second structure is more complex, involving what is referred to as the phenomenon of narrative generation. This approach incorporates intricate elements such as characters and situations.